2013
DOI: 10.1200/jco.2012.45.9271
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of Hospice Care by Medicaid-Insured Patients With Stage IV Lung Cancer in New York and California

Abstract: Purpose Medicare patients with advanced cancer have low rates of hospice use. We sought to evaluate hospice use among patients in Medicaid, which insures younger and indigent patients, relative to those in Medicare. Patients and Methods Using linked patient-level data from California (CA) and New York (NY) state cancer registries, state Medicaid programs, NY Medicare, and CA Surveillance, Epidemiology, and End Results–Medicare data, we identified 4,797 CA Medicaid patients and 4,001 NY Medicaid patients ages 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 19 publications
1
54
1
Order By: Relevance
“…From the literature on MCCCs at end of life, the findings are sparse and inconsistent. Adult researchers have reported no relationship between MCCCs and hospice utilization, 13,14 while others have found a significant decline in the proportion of patients with multiple conditions using hospice care. 15 Initial work examining pediatric MCCCs at end of life has been primarily descriptive and methodological.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature on MCCCs at end of life, the findings are sparse and inconsistent. Adult researchers have reported no relationship between MCCCs and hospice utilization, 13,14 while others have found a significant decline in the proportion of patients with multiple conditions using hospice care. 15 Initial work examining pediatric MCCCs at end of life has been primarily descriptive and methodological.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Nonelderly adults are also less likely to receive palliative and/or hospice services prior to death. 6,11 From the pediatric perspective, the majority of children who die from cancer die in the initial treatment phase, in the hospital, in an ICU, while still receiving aggressive curative therapies (e.g., chemotherapy). [12][13][14][15][16][17] Preliminary evidence from adolescents at the end of life suggests that they prefer to die at home, yet the vast majority die in a hospital setting.…”
Section: Introductionmentioning
confidence: 99%
“…54,55 Unfortunately, most US patients who receive hospice care are referred too late for hospice care to exert its full benefit, and many patients are never referred at all. 49,53,56 Several groups have examined patterns in referrals to hospice care. A recent study at an academic medical center showed marked and unwarranted variation in hospice LOS within divisions and by doctor.…”
mentioning
confidence: 99%